Opioid-Sparing Anesthetic Strategy with Ultrasound-Guided Superficial Cervical Plexus Block in Pediatric Recurrent Lymphangioma Surgery: A Case Report - Rofiudin Ali; Rudy Vitraludyono; Buyung Hartiyo Laksono; Muhammad Farlyzhar Yusuf (HM Publisher, 2026)
Introduction: Pediatric cervical mass surgery presents unique perioperative challenges, including airway proximity, hemodynamic lability, and the need for effective opioid-sparing analgesia. The superficial cervical plexus block (SCPB) targets the cutaneous branches of C2-C4 emerging at the posterior border of the sternocleidomastoid muscle, but its use in pediatric oncologic neck surgery is infrequently reported. Case presentation: A 9-year-old girl (24 kg) presented for excision of a progressively enlarging recurrent right cervical mass clinically and radiologically suggestive of a multiloculated lymphatic malformation. After balanced general anesthesia with endotracheal intubation, an ultrasound-guided right SCPB was performed using 8 mL of ropivacaine 0.2% with dexamethasone 5 mg as an adjuvant. The 2-hour excision proceeded with stable hemodynamics, no additional intraoperative opioid requirement after a single induction-phase fentanyl dose, and a positive fluid balance of +40 mL. The patient was extubated uneventfully, recovered in the post-anesthesia care unit (PACU) without rescue analgesic demand, and was transferred to the ward on postoperative day 1 with excellent analgesia and no neurologic, respiratory, or wound complications. Conclusion: Ultrasound-guided SCPB combining low-concentration ropivacaine with perineural dexamethasone provided effective opioid-sparing analgesia for pediatric cervical lymphangioma excision while preserving respiratory reserve and hemodynamic stability. Compared with previously published pediatric SCPB cases — predominantly in vocal cord, otologic, and tympanomastoid surgery — the present report extends documented experience to recurrent oncologic cervical mass excision, contributing to the developing pediatric regional anesthesia literature in the Indonesian and broader Asian setting.